Energy efficient production planning and scheduling problem with processing technology selection. (June 2019) - Liang, Jingran; Wang, Yuyan; Zhang, Zhi-Hai; Sun, Yiqi
Highlights: A capacitate production planning and scheduling problem with energy concerns is studied. An efficient fix and optimize heuristic algorithm is proposed. The numerical study illustrates that larger number of techniques contributes to cost reduction. The case study demonstrates that large declines of total and energy cost are made by applying the proposed algorithm. Abstract: Energy efficiency attains increasing attention in production systems due to growing energy costs and public perception of environmentally conscious operations. The paper features a capacitated production planning and scheduling problem (CPPS) with sequence-dependent setups for a continuous production line. Meanwhile, energy consumption costs associated with process techniques selection decisions are incorporated into the CPPS. A fix-and-optimize solution approach is proposed to solve the problem. Extensive computational experiments reveal an advantage of the proposed approach having a stable computational performance in solution quality. The optimal results also show the energy cutting benefits of the integrated decision considering operations and energy costs. Moreover, a case study of tea drink production line is presented to demonstrate the application of the model and the solution approach.